EMPLOYER BRANDING STRATEGY FOR TECHNOLOGY TALENT ACQUISITION AMONG GENERATION Z IN COOPERATIVES - Sekar Widyasari Putri; N. Azizia Gia Mutiara Sari; Bambang Agus Sumantri; Candraningrat Candraningrat (Universitas Nahdlatul Ulama Surabaya, 2026)
This research begins with the disruptive phenomenon of digitalization and the changing characteristics of the workforce. This phenomenon has resulted in a war of talent. Organizations are competing to recruit talent who have mastery of technology to accelerate technological adaptation within the organization. The purpose of this research is to identify the ideal employer branding model to implement to help Cooperatives attract top talent and accelerate technological adaptation. The novelty of this research lies in the application of employer branding to the talent acquisition process for digital natives, namely Generation Z, in Cooperatives. An exploratory qualitative approach was used to identify the ideal employer branding model for Cooperatives to acquire Generation Z talent. Qualitative data were obtained from in-depth interviews with cooperative leaders, employer branding experts, and Generation Z. This research contributes to talent management at the talent acquisition stage. The results of the study. This study proposes the CARES (Collective Purpose, Active Participation, Real Experience, Empowering Growth, Sustained Belonging) framework as a cooperative employer branding model that is relevant to the characteristics of Generation Z. The CARES framework positions employer branding not merely as a recruitment tool, but as a strategic mechanism to build value alignment, long- term engagement, and the regeneration of cooperative talent. With this approach, cooperatives have the potential to position themselves as an alternative workplace that is meaningful, participatory, and sustainable amidst the dynamics of the digital labor market.